Clinical instructors' Motivational roles and perceived effect on absenteeism among student nurses in a tertiary hospital, Benin-City, Nigeria - Olaolorunpo Olorunfemi; Rachael Olufunmilayo Oduyemi; Christiana Olanrewaju Sowunmi; Vitalis Okafor; Lucy O Chukwuka; Ngozi Rosemary Osunde; Achi Favour Ezinne (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Absenteeism is a situation whereby students absence themselves from clinical posting without good reason, this incidence among student nurses contributed a significant problem that if not addressed will adversely affect the quality of nursing care; therefore, motivation of student during clinical posting found to be an important ingredient needed in eradicating absenteeism. Consequently, this study aims to determine the reasons why student nurses absenting themselves from clinical posting, its effect and how clinical instructor can motivate student nurses since they are the first role models and have a significant impact in their skill development. MATERIALS AND METHODS: A descriptive, quantitative design was used to elicit the information from a sample of 80 nurses and 80 students' nurses. Nurses: 25 medical surgical ward, 23 surgical ward, 17 obstetrics and gynecology ward, 15 theaters, and 80 student nurses, statistically drawn through a stratified sampling technique across the wards and school of nursing. Data collected were analyzed using tables, percentages, means, and standard deviation at 0.05 level of significance through the Statistical Package for the Social Sciences software. RESULTS: The student participants reported that non conducive working environment, working in infectious ward without adequate protection, noncooperation from clinical instructor, excessive number of clinical hours, embarrassment faced in front of patients and other medical personnel, lack of prompt medical treatment and care when sick, too much workload, and other number of clinical assignments as a major reason why they absenting themselves from clinical posting. The effect of student absenteeism and how students can be motivated is identified in this study. CONCLUSION: Reported factors leading to absenteeism among nursing students and identified motivating care should be handled carefully by the hospital managers to produce better health-care delivery' nurses in future.